Didactica – Typography for children’s didactic books - Casarini, Paula Cristina; Farias, Priscila Lena (InfoDesign, 2008)
This paper summarizes the results of an undergraduate final research that aimed to the development of a typeface for didactic books recommended for children in the process of literacy, between 7 and 8 years. It is believed that the use of such typeface facilitates the process of reading to children, making subtler the introduction of didactic books to their daily lives, which can result in encouraging the practice of reading. The methodology research on literacy and children's textbooks, as well the analysis of other typefaces developed for children. Based on the research and analysis, a new sans-serif typeface, with peculiar features, was developed, and is presented throughout this work.